Estudo da ativação via carbonatação acelerada da escória granulada de alto forno (EGAF) para a produção de ligante especial - Vargas, Camile de (2023)
The production of clinker, the main raw material for Portland cement, requires a temperature of approximately 1450°C for calcining the raw materials, with high consumption of limestone and clay and high CO2 emissions. In this scenario, the need to develop cementitious materials with lower environmental impact is strengthened. This work aimed to study the activation by accelerated carbonation of granulated blast furnace slag (EGAF) for the production of a special binder. The experimental program was developed in two stages: in the first stage, the carbonation chamber was developed to carry out the process of accelerated carbonation of EGAF; in the second stage the EGAF-based mortar specimens (CPs) were prepared to be submitted to accelerated activation by CO2. Cylindrical PCs (3 cm diameter and 5 cm height) were molded with a mass ratio of 1:3 (EGAF and quartz sand), sand (equally divided into four granulometries: 1.2; 0.6; 0,30; 0.15 mm), and water/dry materials ratio of 0.10. The CPs were subjected to CO2 at a constant pressure of 1 bar in the CO2 accelerated carbonation chamber, with exposure temperature (20°C, 40°C and 60°C) and CO2 activation time as study variables (2h, 4h and 6h). Reference samples (not exposed to accelerated CO2 activation) were prepared and kept in an acclimatized room at 20°C with a relative humidity of 65%. Compressive strength tests were performed on the CPs at ages 14 and 28 days. Mineralogical (DRX) and morphological (SEM) analyzes of the samples were performed at the age of 14 days. The compressive strength results indicated that both the increase of temperature, from 20°C to 40°C and from 20°C to 60°C, and the increase of exposure time, from 2h to 4h and from 2h to 6h, as well as the interaction between the two variables in the CO2 accelerated activation process had a significant effect in increasing the strength of the samples. The average compressive strength of the samples cured at 20°C for 2h at the age of 14 days was 1.40 MPa. On the other hand, the average compressive strength of samples cured at 60°C for 6h at the age 28 days was 6.27 MPa. This was the highest average compressive strength obtained. Nevertheless, as the statistical analysis did not result in a significant difference between the strengths of the samples 60°C/6h and 60°C/4h, this indicates that the optimized process conditions would be at 60°C/4h. This behavior corroborates the increase densification of the matrix verified with the SEM, which happened similarly at 60°C/4h and 60°C/6h. With the help of XRD, calcite and aragonite crystalline phases were identified in the samples submitted to accelerated carbonation. These phases were not identified in the control samples (without carbonation process), which showed an average compressive strength, at 28 days of 0.59 MPa.